Bowel MRI imaging to investigate drug delivery from coated capsules - Sulaiman, Sarah (2023)
Background Magnetic resonance imaging (MRI) has the potential to provide new physiological insights into oral dosage forms in the undisturbed human GI tract. This potential has been recently shown in the literature, however these initial studies principally focused on the upper GI tract. Applications to the lower GI tract and particularly to MRI imaging of coated capsules remain to be explored to date.